MAQASID SYARIAH DALAM WAKAF SAHAM - Sitta 'Ala Arkham (Fakultas Syariah (Syari'ah Faculty ), 2020)
Maqasid Shariah of waqf is to provide the maximum benefit with remaining the object of waqf. In order, to provide greater benefits, development is needed in the management and object of the waqf itself. Waqf stock become one of the development models of object waqf. The spirit of waqf development should be accompanied by maintaining the purpose of waqf, the existence of waqf stock practice needs to be reviewed from maqasid shariah, so the waqf stock innovations remain in the corridor and do not deviate. There are two models of management in waqf stock, first; capital gain and dividen from stocks as waqf, secondly; the stock as an object of the waqaf itself. This paper is a qualitative study, using the maqasid shariah approach as method. The results showed that the first model is still in accordance with the maqasid shariah - this is attributed to the waqf money. The second model, still conforms to the maqasid shariah by extending its meaning to the immortality of the waqf object, from the former preserving the sum of the shares to the value of the stock, and the istibdal method of the second model.